Assessment of the impact of traffic conditions on the availability of transport services of the city bus route - Vdovychenko, Volodymyr; Ivanov, Igor; Pidlubnyi, Serhii (Technology audit and production reserves, 2022)
The object of research is the influence of the conditions for the implementation of technological trip operations in the implementation of the priority movement of urban passenger transport on the bus route on the level of accessibility of the transport service. On the basis of the developed contour of information communication, a typical procedure for establishing the parameter for assessing the availability of a transport service, depending on the time indicators of traffic on the route, is singled out. As a controlled parameter that determines the conditions for increasing the availability of a transport service, the trip time and the range of deviations in the arrival of buses to the stopping point are singled out. Implemented on the basis of simulation modeling, the procedure for establishing the correspondence between the time parameters of the departure of buses from the stopping point and the formation of demand made it possible to establish patterns of changes in the level of accessibility of the transport service depending on the traffic conditions on the route. In the course of field observations along route No. 115e «Gagarin avenue metro station – Nesterov street» (Kharkiv, Ukraine) it was found that the introduction of free traffic conditions that meet the conditions of the priority of urban passenger transport can reduce the duration of the trip by 5 min and reduce the range of deviation of the arrival of buses to the stopping point by 4 min. On the basis of experimental studies, it was found that by reducing the duration of the trip from 32 min up to 27 min it is possible to increase the value of the transport service accessibility indicator by 20.5 %. When organizing traffic according to a schedule, it is possible to increase the indicator of the availability of transport services up to 0.679 (by 6.8 %). The introduction of priority traffic on route No. 115e allows reducing the trip time to 22–27 min, which will positively affect the indicator of the availability of transport services (increase to 0.803 in traffic without a schedule and up to 0.880 in compliance with the traffic schedule). Reducing the range of bus arrival deviations in the range from –1 min up to +2 min allows increasing the level of accessibility of transport services under normal conditions from 6.8 % to 13.3 %, and with the introduction of priority traffic – from 15.4 % to 18.3 %.